Genetic analysis of trends in production traits of Sahiwal cows over years using BLUP animal model - Parveen, KAISER; Gupta, A.K; Gandhi, R.S.; Chakravarty, A.K; Mumtaz, Shabahat (Indian Journal of Dairy Science, 2018)
An investigation on first lactation performance records, of 820 Sahiwal cows, maintained at NDRI, Karnal, (1962-2015) was conducted to study the effect of genetic and non-genetic factors, to estimate genetic parameters and genetic trends of production traits over years by regression method using animal model. The traits considered were FL305DMY, FLTMY, FLL, AFC and FCI. The overall least squares means for FL305DMY, FLTMY ,FLL, AFC and FCI were 1972.50±64.72 kg, 2070.41±79.20 kg, 323.171±7.22 days, 1114.21±9.14 days and 444.40± 5.41days, respectively. Sire and year of calving had significant effect on all the traits. Month of birth/calving had significant effect on all the traits except FLTMY. Age at first calving have significant effect on all the traits except FCI where as service period have significant effect on all the traits included in the model. The heritability estimates of AFC, FL305DMY, FLTMY, FLL and FCI were 0.45±0.14, 0.18±0.11, 0.19±0.10, 0.16±0.09 and 0.03±0.08 respectively. The phenotypic trends in AFC, FL305DMY, FLTMY, FLL, and FCI were -0.05±0.315, 19.85±2.17, -26.06±2.4, -3.22±0.26 and 0.041±0.47, respectively. Genetic trends were positive, significant and in desirable direction in production traits. The regression coefficients for the phenotypic trend of first lactation 305-days or less milk yield and first lactation total milk yield were -19.85±2.17 kg per year and -26.06±2.4 respectively. The regression coefficients showed the positive annual genetic gain of 1.72 kg and 2.08 kg for FL305DMY and FLTMY respectively. On the contrary the environmental trends were negative for both FL305DMY (-21.57±2.2) and FLTMY (-28.14±2.49). All the trends values were statistically significant (p